Innovation: Their Modern Significance - Ametovna, Aliyeva Elnara (Research Parks Publishing LLC, 2023)
The article proves that it is the intellectual potential that is the main factor in the innovative development of both the enterprise and the entire civilization. The dependence of the given direction of innovative development on the intellectual factor of innovative potential is also revealed. Based on logical reasoning, the author offers his own definition of the terms «lost innovation», «the law of innovation creation», as well as a modern definition of the term «innovation».